2015
DOI: 10.1007/s11356-015-4120-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxic effects of monocrotophos, an organophosphorous pesticide, on zebrafish (Danio rerio) embryos

Abstract: The present study examined the response of zebrafish embryos exposed to different concentrations (10, 20, 30, 40, 50, and 60 mg/L) of monocrotophos under static conditions for 96 h. We found that mortality had occurred within 48 h at all test concentrations, later insignificant mortality was observed. Monocrotophos (MCP) can be rated as moderately toxic to the Zebrafish embryos with a 96-h median lethal concentration (LC50) of 37.44 ± 3.32 mg/L. In contrast, it greatly affected the development of zebrafish emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Ali et al (2014) also reported the time-dependent and dose-dependent increase of genotoxicity of an OP insecticide, dimethoate in C. punctatus, which were found to be highly correlated with oxidative stress. Our results along with those of Pamanji et al (2015) mentioned earlier, provide information on the toxic effects of MCP in both the adults and embryos of zebrafish suggesting that MCP can affect zebrafish at any time during its life cycle. Organophosphate pesticides such as MCP and those cited above cause the alkylation of DNA bases either directly or indirectly by protein alkylation leading to DNA disintegration (Bhinder and Chaudhry 2013).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Ali et al (2014) also reported the time-dependent and dose-dependent increase of genotoxicity of an OP insecticide, dimethoate in C. punctatus, which were found to be highly correlated with oxidative stress. Our results along with those of Pamanji et al (2015) mentioned earlier, provide information on the toxic effects of MCP in both the adults and embryos of zebrafish suggesting that MCP can affect zebrafish at any time during its life cycle. Organophosphate pesticides such as MCP and those cited above cause the alkylation of DNA bases either directly or indirectly by protein alkylation leading to DNA disintegration (Bhinder and Chaudhry 2013).…”
Section: Discussionsupporting
confidence: 79%
“…A few studies have been carried out on the different effects of MCP on zebrafish such as the estrogenic and feminizing effects of MCP (Zhang et al 2013) and cortisol-mediated stress responses (Zhang et al 2015). In a recent study, different concentrations of MCP were used to evaluate the developmental response of zebrafish embryos (Pamanji et al 2015). Mortality was observed in all the test concentrations along with a large number of morphological abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in previous studies assessing the effects of difenoconazole and cyhalofop-butyl in zebrafish larvae (Mu et al 2013;Cao et al 2016). Early-life stage sensitivity can be argued by the lack of a fully developed metabolic pathway and chorion protection that might decrease the uptake of hazardous substances into the embryo (Fent and Meier 1992;Pamanji et al 2015a). At 48 hpf, 2,4-D did not induced any cardiac disruption, as observed for other pesticides like diuron and diazinon (Velki et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Another study in porcine ovarian cells demonstrated that both malathion and diazinon decrease the efficiency of in vitro maturation of porcine oocytes and damage early embryo development (Ducolomb et al 2009). More recently, evidence of OP developmental toxicity in zebrafish suggested various teratogenic effects and increased death of embryos (Pamanji et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…2009 ). More recently, evidence of OP developmental toxicity in zebrafish suggested various teratogenic effects and increased death of embryos ( Pamanji et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%